Research on Outdoor Space Design Strategy of “SOS Children's Village” Based on the Psychology of Troubled Children - Fu, Fei; Liu, Xiao; Zhou, Sixiang (Frontiers in Public Health, 2022)
Despite significant interaction between children's psychology and space in welfare institutions, only a handful of empirical studies have focused on it to date. Through the investigation, analysis, and spatial classification of the psychological issues of troubled children in the SOS children's village community in Chengdu, we observed the records for 1 year and used the PHCSS-SD method innovatively to systematically and quantitatively analyze the psychology of troubled children and their perception of public space in the park. Based on the needs of hearing, vision, touch, interaction, and safety of children in distress, we selected nine evaluation factors, including daylighting, interesting pattern, participation, and touchability. Each factor was categorized into five evaluation scales for psychological measurement and analysis to provide a basis for the development of mental health and the optimization of the living environment of children in distress. Based on the SD broken line of public space, we analyzed the advantages and disadvantages of space and affirmed the crucial contributions made by the Chinese government to children's welfare. Overall, this study discusses the strategy of building outdoor public spaces in the SOS children's village community.